The Imam’s Knowledge (`Ilm) to the Quran and Its Quality - Mahmud Ghayumzadeh; Muhammad Taghi Shaker (آموزه‌های قرآنی, 2013)
From the perspective of ImamÌ, the Imam has divine knowledge, hence His guiding role comprises the insight (seen and unseen) of the society and all of the men. The verses and traditions obviously prove the divine knowledge of the Imam. The present paper analyzes one of these knowledge sources. The traditions have stated that the Quran is one of the rich sources for the extensive knowledge and awareness of the Imam. They have derived their knowledge to the truthfulness and inner meanings of the Quran from the Prophet teachings and He has interpreted and analyzed the Quranic teachings in a definitive function. Therefore, the Imam is a parameter to solve polarities and declaring the Prophet teachings. However understanding the truthfulness of the Quran has different origins and provenance, the Imam has derived those beneficiaries from God, because He has determined the Imam this position.